Stress corrosion cracking behavior of austenitic stainless steels in natrium chloride solutions - Samir Milad, Elsariti
Stress Corrosion Cracking is an environmentally assisted failure caused by contact to a corroding while under a sustained tensile stress. Stress Corrosion cracking is most often rapid, unpredictable and catastrophic. Failure can occur in as little as a few hours or take years to happen. Most alloys are susceptible to Stress Corrosion Cracking in one or more environments requiring careful consideration of alloy type in component design. In aqueous chloride environments austenitic stainless steels and many nickel based alloys are known to perform poorly. One of environment is Natrium Chloride. This contains natrium chloride with concentration 3.5wt% NaCl and 9.35wt% NaCl. Austenitic stainless steel is usually used in distillation construction tank and pipe line in many different industries especially petroleum. So, Austenitic stainless steel has been used as a substitute for carbon steel in corrosive environments, however, brittle type failures were encountered due to stress corrosion cracking. Stress Corrosion Cracking in natrium chloride solution is one of the most prevalent forms of Stress Corrosion Cracking in Austenitic Stainless Steels. Component life prediction requires Stress Corrosion Cracking initiation and failure time from published data, however, such data are limited. In this research, experimental equipments were used for gathering data on the incubation period and the crack time about last of 70 days for types 304, 310 & 316 Austenitic Stainless Steels immersed in 3.5wt% & 9.35wt% NaCl solutions at room temperature which is similar to Sea water and Sabkha (salt-flat). The use of the equipment was verified by conducting a standardized test. The experiment uses a spring loaded fixture type and is based on ASTM G49 for experiment method, and E292 for geometry of specimen. The stress corrosion cracking of the austenitic stainless steels of types 304, 310 and 316 in natrium chloride solution at room temperature is investigated as a function variation of chloride concentration, using a constant load method with one of initial tensile stress as 90% yield strength. Potential scans of selected types of Austenitic Stainless Steels were performed in an attempt to determine the Stress Corrosion Cracking and also they were tested to conduct their mechanical and chemical properties by using such as Scanning Electronic Microscopy and Universal Testing Machine. Detail equipment being used and justification of results obtained are explained in full details in this thesis. In production process, concentration of natrium chloride in sea water and sabkha (salt-flat) become more effective to those industries since those are the surrounded environment. And that reason is that the experiment is conducted in natrium chloride concentration such as 3.5wt% and 9.35wt% NaCl. Pitting corrosion occurs on the surface of specimen’s notch area in different stages on different types of those selected Austenitic Stainless Steels. Austenitic Stainless Steel 304 was more susceptible for all conditions. In natrium chloride solution with concentration of 3.5wt%, all specimens do not show any cracking for first stage of 404 hour of test time. The higher concentration natrium chloride and the same stress level, the crack speed increase with same time failure. And recommendations for future experimental work are presented herein.